2022
DOI: 10.1111/ijpo.12901
|View full text |Cite
|
Sign up to set email alerts
|

Healthy lifestyles and physical fitness are associated with abdominal obesity amongLatin‐Americanand Spanish preschool children: A cross‐cultural study

Abstract: Summary Background Identifying environmental factors that influence health in children are necessary to develop preventive strategies. Objective To determine the association between the lifestyles of children (i.e., Mediterranean diet (MD), physical activity (PA), fitness and screen time (ST) with abdominal obesity (AO) of preschoolers from three Spanish‐speaking countries (Chile, Colombia and Spain) with different socioeconomic levels and Human Development Index (HDI) indicators. Material and Methods This cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
2
7
0
1
Order By: Relevance
“…Firstly, with regard to descriptive analysis, it was observed that most of the students from analysed school, 80.8%, engage in PA out of scholar hours compared to 19.2% of sedentary pupils. This data reveals that the percentage of physically active children is large, in line with recent research on the school population in our Spain [34,35,36].…”
Section: Discussionsupporting
confidence: 90%
“…Firstly, with regard to descriptive analysis, it was observed that most of the students from analysed school, 80.8%, engage in PA out of scholar hours compared to 19.2% of sedentary pupils. This data reveals that the percentage of physically active children is large, in line with recent research on the school population in our Spain [34,35,36].…”
Section: Discussionsupporting
confidence: 90%
“…Accordingly, in a randomized, parallel trial of children aged 3–5 years old, high MD adherence resulted in a reduction in BMI after one year and at the end of the follow-up interval [ 69 ]. A cross-sectional study including 982 schoolchildren at the age of 4–6 years from Chile, Colombia, and Spain has also documented that a better lifestyle, including higher MD adherence, was significantly associated with a lower risk of abdominal obesity [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Este dato revela que el porcentaje de alumnos físicamente activos es amplio, lo que concuerda con lo publicado en recientes investigaciones sobre población escolar en nuestro país. (Melguizo et al, 2021;Rodríguez-Fernández et al, 2021;Latorre et al, 2022). Por el contrario, los valores obtenidos en nuestro Colegio difieren de los hallados por Alfonso-Rosa et al ( 2018), para quienes, en un mismo grupo de población, la mayoría de los alumnos estudiados eran sedentarios.…”
Section: Discussionunclassified